(untitled) (Ta’limning zamonaviy transformatsiyasi, 2024)
Annotation: The digital economy is now the cornerstone of global economic development, significantly transforming traditional business practices. Technology-driven management systems and strategies have replaced conventional approaches, bringing efficiency and innovation to business processes. In this context, mobile technologies have become vital tools, simplifying economic interactions, increasing speed, and improving organizational processes. This thesis explores the unique aspects of business management in the digital economy, the opportunities provided by mobile technologies, and their impact on human lives.